IMPLEMENTASI KEBIJAKAN BANTUAN DANA KHUSUS DESA BERMASA DALAM UPAYA MENINGKATKAN INFRASTRUKTUR DI DESA TAMERAN KECAMATAN BENGKALIS TAHUN 2022-2024 - Restiana, Nadia; Pane, Rico Purnawandi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Tameran Village is one of the villages that is included in the category of independent villages, related to the availability of infrastructure also supports the welfare of the community, where in Tameran Village itself there are still many complaints from the community regarding the availability of inadequate infrastructure. There are still many potholed roads leading to residents' homes, while these roads are access for residents to earn a living and are a daily route for children to go to school, until now there has been no response from the Village government to try to fix the road. Even though the local government has provided assistance related to village financial assistance of 1 billion, in accordance with Bengkalis Regent Regulation Number 74 of 2021, Article 5 explains that 60% of the funds are used for village development or village infrastructure. The purpose of this study is to describe the Implementation of the Special Village Fund Assistance Policy in an Effort to Improve Infrastructure in Tameran Village, Bengkalis District in 2022-2024. In this study, the theory used is the theory of Edward George III, according to him there are four variables in the policy itself, namely communication, resources, disposition or attitude of the implementer and communication structure. The four variables must be implemented simultaneously because one has a close relationship with the other. The results of this study indicate that the Implementation of the Special Village Fund Assistance Policy in Tameran Village has not been running optimally, because there are influencing factors such as communication, resources, position, and bureaucratic structure, which have caused the process of activities carried out by the village government to not be optimized properly. Keywords: Implementation, Policy, Village, Massive